Upaya Guru dalam Meningkatkan Keterampilan Berbicara Siswa Kelas 3 SD Hikmah 1 Yapis Jayapura - Samuel Mamonto; M. Fitrah Pratama (Departement of Mathematics Education, 2024)
This research aims to improve the speaking ability of students in third grade at SD Hikmah I Yapis Jayapura as well as the teacher's efforts, namely 1). The teacher uses storytelling strategies, 2). The teacher uses group discussion strategies, 3). Children repeat the story that the teacher has told, 4). The teacher provides motivational rewards in the form of